About methods of the substantiation of an allowable risk level - Perelmuter, Anatoly V. (Journal of Civil Engineering and Management, 2000)
The problem of admissible risk optimisation is described in detail, especially for the case of possible human victims. Different points of view on the problem of “human being cost” are compared, and the approach based on comparing the numbers of saved lives and the risk for the persons, providing the life saving are considered. An information on actual risk level for different kinds of human activities is presented. The mathematical model of creating the public opinion in case of accidents and analysis of changing the function of society discomposibility function in time are presented. Effects commonly ignored during risk estimation are analysed – like departure from the principle of equal providing the risks for objects of equal responsibility, but different quantity and presence of non-linear dependence between the severity of accidents and public reaction.Apie leistino rizikos lygio pagrindimo metodusSantrauka. Analizuojama leistino rizikos lygio optimalaus parinkimo užduotis, ypač tais atvejais, kai galimos žmonių aukos. Lyginami skirtingi požiūriai į žmogaus gyvybės kainos problemą nagrinėjamas požiūris, kuris remiasi išgelbėtų gyvybių skaičiaus palyginimu su ta rizika, kuri tenka žmonėms, atliekantiems gelbėjimo darbus. Pateikiama informacija apie realios rizikos įvairiose žmonių veiklos srityse lygį. Aprašomas visuomenės nuomonės formavimo avarijos atveju matematinis modelis ir analizuojami visuomenės reakcijos pokyčiai laikui bėgant. Aprašomi efektai, šiaip jau ignoruojami vertinant riziką taip pat avarijos mastelio efektas, nurodoma nelinijinė nelaimingo atsitikimo masto priklausomybė nuo visuomenės reakcijos.Article in Russian.First Published Online: 26 Jul 2012